Critical peer feedback for business English writing using Qzone Weblogs among Chinese undergraduates / Gao Xianwei - Gao, Xianwei (2017)
This study aims to investigate how critical peer feedback improves the quality of peer feedback and Business English Writing. Based on the theoretical framework of Sociocultural Theory and Zone of Proximal Development, “Critical Peer Feedback” is defined by the concepts of “critical thinking” and “peer feedback”. The mechanism of critical peer feedback is explored by participants’ perceptions, process, contents, and factors of critical peer feedback. This study is conducted in the environment of online Qzone weblog. The online features of Qzone weblog are studied to explore how they affect critical peer feedback to improve Business English Writing. A qualitative case study is conducted in this study with a group of six participants of Chinese undergraduates for one semester duration. Three types of data are collected including semi-structured interviews, Business English Writing assignments, and artifacts of critical peer feedback. The data are analyzed by QSR NVivo 8.0 with the content and thematic analyses. The codes are quoted at descriptions, and the nodes and models are illustrated with visualization in findings. The findings reveal that “critical peer feedback” improves the quality of peer feedback, and the quality of Business English Writing among Chinese undergraduates. The participants prefer Revised Bloom’s Taxonomy of critical thinking skills for critical peer feedback. Critical peer feedback follows a four-step mental process in Business English Writing. The eight issues in critical peer feedback are perceived in this study. Qzone weblog is believed to be a reasonable information and communication technology (ICT) platform for critical peer feedback, and the most popular weblog among